Pengembangan Alat Peraga pada Materi Listrik Sederhana untuk Meningkatkan Pemahaman Siswa Kelas IV di Mi Mifathul Huda Mlokorejo Jember - Agil Meytha, Ayunda; Hidayat, Kahfianto; Fatimatus Zahro , Lilis; Suwignyo Prayogo, Muhammad (Universitas Islam Jember, 2024)
Visual aids are part of learning resources that contain processive material in the student environment, which are graphic, photographic or electronic tools, which are used to capture, process and reconstruct visual or verbal data. In this research, the learning media used are simple electrical teaching aids, which are used to help explain examples of the electrical apparatus itself. The approach used in this research is a qualitative approach, in which researchers conduct research on the development of simple electrical teaching aids. Data collection techniques were by means of interviews, observations, questionnaires, and also tests held at MI Mifathul Huda Mlokorejo Jember. The results obtained in this research were a high level of student interest in the teaching aids provided, as well as student understanding which was proven by carrying out tests carried out carried out given to students at MI Mifathul Huda Mlokorejo Jember. The use of teaching aids in simple electrical material can be interesting and provide direct understanding to students. Where students are given real examples and illustrations that are easy for students to understand. However, other game methods are needed so that students who are not paying enough attention can follow the learning process well.